1991
DOI: 10.1042/bj2780155
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical characterization of two isoforms of rat liver ecto-ATPase that show an immunological and structural identity with a glycoprotein cell-adhesion molecule with Mr 105,000

Abstract: One of the cell-adhesion molecules (CAMs) responsible for rat hepatocyte aggregation has been described as a glycoprotein having an Mr of 105,000 (cell-CAM105). The Mr and localization of cell-CAM105 in liver membranes are very similar to those of liver ecto-ATPase, an ATPase with its nucleotide-hydrolysing site localized on the outside of the cell membrane. The protein sequence of the ecto-ATPase has been deduced from cDNA cloning. Structural analysis of the sequence indicates that the ecto-ATPase has immunog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
1
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 27 publications
0
57
1
1
Order By: Relevance
“…On the basis of such results, a tumor suppressive role for CEACAM1 has been postulated. Conformingly, CEACAM1 overexpression in different prostate cancer cell lines used in experimental tumor models in mice reduced tumor growth without affecting the proliferation of tumor cells themselves (Lin et al, 1991). Furthermore, it has been reported that the tumor inhibitory function of CEACAM1 depends on the cis-determinants in its cytoplasmic domain (Izzi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of such results, a tumor suppressive role for CEACAM1 has been postulated. Conformingly, CEACAM1 overexpression in different prostate cancer cell lines used in experimental tumor models in mice reduced tumor growth without affecting the proliferation of tumor cells themselves (Lin et al, 1991). Furthermore, it has been reported that the tumor inhibitory function of CEACAM1 depends on the cis-determinants in its cytoplasmic domain (Izzi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…C-CAM1 has sequence homology with carcinoembryonic antigen (Aurivillius et al, 1990;Lin et al, 1991). As predicted from its cDNA sequence, C-CAM1 contains four extracellular Ig-like domains, a transmembrane domain, and a cytoplasmic domain.…”
Section: Introductionmentioning
confidence: 99%
“…Control, sham-operated animals; castrated, castrated animals; +TP, castrated animals treated with testosterone propionate; +TP/F, castrated animals treated with testosterone propionate plus 4-hydroxy¯utamide both were used for the immunohistochemical analyses of rat prostate tissues. These included: Ab669, produced by immunizing rabbits with puri®ed C-CAM protein (Lin et al, 1991), that recognizes both the L-and S-C-CAM isoforms; Mab 5.4, a mouse monoclonal antibody of the IgG1 subtype, that also recognizes both isoforms (Hixson and McEntire, 1989); anti-CL, which is a polyclonal rabbit anti-peptide antibody speci®c for the cytoplasmic domain of L-form C-CAM and was generated by immunizing rabbits with keyhold limpet hemacyanin-conjugated peptides (Lin et al, 1991). We also used a rabbit polyclonal antibody anti-CS, produced against the hexapeptide GGSGSF, which is found only in the cytoplasmic domain of S-form C-CAM (Thompson et al, 1994), and monoclonal antibody K903 or 34bE12 (Keratin-903, isotype IgG, Enzo Diagnostics, Farmingdale, NY, USA), which is speci®c for high-molecularweight cytokeratins 1, 5, 10 and 14, and was used to identify the basal cells of rat prostate.…”
Section: Antibodiesmentioning
confidence: 99%
“…Structures of the VP were studied in a longitudinal plane. Antibodies diluted in phosphate-bu ered saline (PBS) at optimal concentrations, as determined from the rat liver section assays (Lin et al, 1991), were incubated with rat prostate tissue sections at room temperature. IF labeling using mouse monoclonal antibodies was performed by using the ABC kit (Vector Laboratories) as follows: The sections were sequentially blocked in 10% normal goat serum, avidin D, and biotin for 15 min each to decrease nonspeci®c staining.…”
Section: Immunohistochemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation